The Method for Measuring Loop Resistance in Gas Insulated Substation - Li Zhou; Tiecheng Lu; Bo Zhang; Guangkai Yu; Jiawei Wan (Institute of Advanced Engineering and Science, 2014)
This paper studies the method for measuring the loop resistance of GIS conductor pole basing on the super capacitor producing impulse current up to several thousand amperes. This method overcomes the limitations of conventional diagnostic method. Typical GIS conductor poles are chosen. Based on FEA and lab tests, the effect of different forms of current and contact condition, relationship between the temperature of contact and the loop resistance is researched. In full-scale testing under realistic operating conditions on the new 220 kV GIS using prototype instrumentation a very good sensitivity in an early stage was obtained.